Connective Tissue Disease-associated Interstitial Lung Disease: A review - Gutsche, Markus (2012)
Interstitial lung disease (ILD) is commonly encountered in patients with connective tissue diseases (CTD). Besides the lung parenchyma, the airways, pulmonary vasculature and structures of the chest wall may all be involved, depending on the type of CTD. As a result of this so-called multi-compartment involvement, airflow limitation, pulmonary hypertension, vasculitis and extrapulmonary restriction can occur alongside fibro-inflammatory parenchymal abnormalities in CTD. Rheumatoid arthritis (RA), systemic sclerosis (SSc), poly-/dermatomyositis (PM/DM), Sjögren’s syndrome (SjS), systemic lupus erythematosus (SLE), and undifferentiated (UCTD) as well as mixed connective tissue disease (MCTD) can all be associated with the development of ILD. Non-specific interstitial pneumonia (NSIP) is the most commonly observed histopathological pattern in CTD-ILD, but other patterns including usual interstitial pneumonia (UIP), organizing pneumonia (OP), diffuse alveolar damage (DAD) and lymphocytic interstitial pneumonia (LIP) may occur. Although the majority of patients with CTD-ILD experience stable or slowly advancing ILD, a small yet significant group exhibits a more severe and progressive course. Randomized placebo-controlled trials evaluating the efficacy of immunomodulatory treatments have been conducted only in SSc-associated ILD. However, clinical experience suggests that a handful of immunosuppressive medications are potentially effective in a sizeable portion of patients with ILD caused by other CTDs. In this manuscript, we review the clinical characteristics and management of the most common CTD-ILDs.